The impact of vocabulary instruction on vocabulary achievement - Anisa Mutia; Rosnani Sahardin; Geunta Mardika Putra (Universitas Syiah Kuala, 2022)
Students must have a sufficient vocabulary size in order to improve other English skills, as vocabulary is one of the most crucial aspects of language acquisition. Therefore, it is necessary to teach vocabulary when teaching a language. This study seeks to determine the effect of vocabulary instruction on vocabulary achievement among senior high school students. This study was a quantitative study, the sample was 30 students, and the data was collected using a pre-test and post-test. Between the assessments, a seven-hour vocabulary education was provided. Using the paired sample t-test and Wilcoxon signed rank test, it was determined whether there was a statistically significant difference between students' scores before and after the vocabulary training was implemented. The results indicate a significant increase in vocabulary scores among students. The results of the research indicate that explicit vocabulary instruction should be incorporated into the teaching and learning process since it has been shown to increase students' vocabulary.